2016
DOI: 10.1016/j.paid.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Knowing what you know: Intellectual humility and judgments of recognition memory

Abstract: This study examined the relationship between recognition memory and intellectual humility, the degree to which people recognize that their personal beliefs are fallible. Participants completed the General Intellectual Humility Scale, an incidental old/new recognition task, and a task that assessed the tendency to over-claim one's knowledge. Signal detection analyses showed that higher intellectual humility was associated with higher discriminability between old and new items, regardless of whether the items we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 12 publications
3
54
1
Order By: Relevance
“…Previous research offers support for links between IH and indicators of learning. For example, IH has been linked to more general knowledge of people, places, and events, and better recognition memory (Alfano et al, 2017;Deffler, Leary, & Hoyle, 2016). This is consistent with the public perception that intellectually humble individuals are knowledgeable and smart (Samuelson et al, 2015).…”
Section: Indicators Of Knowledge Acquisitionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous research offers support for links between IH and indicators of learning. For example, IH has been linked to more general knowledge of people, places, and events, and better recognition memory (Alfano et al, 2017;Deffler, Leary, & Hoyle, 2016). This is consistent with the public perception that intellectually humble individuals are knowledgeable and smart (Samuelson et al, 2015).…”
Section: Indicators Of Knowledge Acquisitionsupporting
confidence: 60%
“…In addition, there is experimental evidence that greater self-perceived knowledge independent of actual knowledge, a potential sign of intellectual arrogance, is associated with overclaiming of knowledge (Atir, Rosenzweig, & Dunning, 2015). Similarly, Deffler et al (2016) found that those low in IH were more confident in their incorrect answers on a recognition memory task than those higher in IH. Thus, it seems that IH may make individuals more accurate at judging what they do not know.…”
Section: Meta-knowledgementioning
confidence: 82%
See 2 more Smart Citations
“…Understanding epistemic goods as character traits or virtues has proved fruitful (Brady and Pritchard , Aikin and Clanton , Battaly , Kidd ). And virtue epistemology offers a place for productive collaboration between philosophers and psychologists (Samuelson et al , Deffler et al , Johnson ).…”
mentioning
confidence: 99%